Integration Strategies of the Union State of Russia and Belarus: Practice of Interaction - N. I. Kharitonova; A. V. Shebanov (Евразийская интеграция: экономика, право, политика, 2025)
Aim. The purpose of the article is to identify practical aspects of the political interaction between Russia and Belarus, implemented within the framework of the integration strategies of the Union State of Russia and Belarus. It is due to the fact that the implementation of integration projects throughout Eurasia is influenced by the transformation of the modern international system. Russia and Belarus have to defend their right to sovereignty and national security and implement integration strategies. Methods. The methodological basis of the work was the institutional approach, as well as the principles of structural functionalism and neo-functionalism in determining the key integration strategies of Russia and Belarus. Results. Based on the methods used, the authors analyzed the stages of Russian-Belarusian economic integration, structured the institutional principles and practices of unification of Russia and Belarus. The novelty of the research lies in the development of predictive development scenarios and recommendations for solving problems of political interaction within the Union State. Results. Based on the analysis, three key scenarios for the development of Russian-Belarusian integration processes are formulated: “positive” (development and strengthening of economic cooperation, as well as the creation of new union institutions, implemented consistently), “neutral” (continuation of cooperation in the format of existing institutions and economic practices), “negative” (conflict relations in the economy and formal activities of the institutes of the SSRB). Conclusions. The authors concluded that a “neutral” scenario with a possible move towards a “positive” one is the most likely. Following the proposed recommendations should lead to a reduction in the impact of problematic aspects of political interaction between the Russian Federation and the Republic of Belarus and the implementation of their integration strategies within the framework of the CBS.